THE EFFECTS OF MAGGOT SECRETIONS ON THE INFLAMMATORY CYTOKINES IN SERUM OF TRAUMATIC RATS - Li, Xiaorong; Liu, Ning; Xia, Xiaoyong; Zhang, Shaochun; Bai, Junlong; Wang, Jiangning (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this study was to analyse the changes of inflammatory cytokines level in traumatic rat serum after the maggot secretions intervention. Acute traumatic rat were randomly divided into three groups that included maggot secretions group, negative group and the control group. TNF-α, IL-6, SOD, LPO levels were measured by radioimmunoassay. The experimental results showed that TNF-α, IL-6, and SOD levels in the model group were significantly increased; LPO level was decreased and showed significant differences. Thus, the content of inflammatory cytokines in acute skin wounds could be reduced by maggot secretions, which play a role in enhancing wound healing.